Properties and applications of nanoparticle/microparticle conveyors with adjuvant characteristics suitable for oral vaccination - Zhang L (Dove Medical Press, 2018)
Lei Zhang,1,2,* Wendi Yang,1,* Chaohua Hu,3 Qianchao Wang,1 Yunkun Wu1,2 1College of Life Sciences, Fujian Normal University, Fuzhou, China; 2State Key Laboratory of Structural Chemistry, Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences, Fuzhou, China; 3National Engineering Research Center for Sugarcane, College of Crop Science, Fujian Agriculture and Forestry University, Fuzhou, China *These authors contributed equally to this work Abstract: Vaccination is one of the most effective approaches in the prevention and control of disease worldwide. Oral vaccination could have wide applications if effective protection cannot be achieved through traditional (eg, parenteral) routes of vaccination. However, oral administration is hampered by the difficulties in transferring vaccines in vivo. This has led to the development of materials such as carriers with potential adjuvant effects. Considering the requirements for selecting adjuvants for oral vaccines as well as the advantages of nanoparticle/microparticle materials as immune effectors and antigen conveyors, synthetic materials could improve the efficiency of oral vaccination. In this review, nanoparticles and microparticles with adjuvant characteristics are described with regard to their potential importance for oral immunization, and some promising and successful modification strategies are summarized. Keywords: oral vaccine, NP/MP conveyors, intestine, antibody, immune response